Counterparty Risk, Impacton Collateral Flows and Role for Central Counterparties - Aitken, James; Singh, Manmohan (Washington, D.C. : International Monetary Fund, 2009)
Counterparty risk in the United States stemming from exposures to OTC derivatives payables (after netting) is now concentrated in five banks?Goldman Sachs, JPMorgan, Bank of America, Morgan Stanley and Citi. This note analyzes how such risks have shifted over the past year. We estimate that the adverse impact of counterparty risk on high-grade collateral flows and global liquidity due to decrease in rehypothecation, reduced securities lending, and hoarding of cash by major banks is at least USD 5 trillion. In order to mitigate counterparty risk, there have been regulatory initiatives to establish central counterparties (CCPs). From a policy perspective, counterparty risk remains large at present and recent experience has shown that OTC derivative positions are not supported by sufficient capital, constituting a major risk for participants in this market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet